PENCEGAHAN TINDAK PLAGIARISME DALAM PENULISAN SKRIPSI: UPAYA MEMPERKUAT PEMBENTUKAN KARAKTER DI DUNIA AKADEMIK - Mulyana Mulyana (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Plagiarism Prevention in Thesis Writing: An Attempt to StrengthenCharacter Building in the Academic World. The study is aimed at describingplagiarism in thesis writing at a tertiary educational institution. The study wasconducted in the Javanese Department, Faculty of Language and Arts, YogyakartaState University. The data were collected through in-depth interviews andobservations, and analysed using the explanatory approach, espesially thequalitative descriptive technique. The findings show that plagiarism in thesiswriting includes duplicating, consisting of (1) duplicating titles, (2) duplicatingcontents, (3) duplicating theories, (4) duplicating, and (5) duplicating references.The process approach in thesis writing can be used to prevent plagiarism. Such anapproach consists of steps as follows: returning the thesis draft, showing originalsources, and cancelling the thesis. These can be carried out by investigating,discussing, evaluating, and presenting thesis titles and contents.Keywords: plagiarism, thesis writing, character building